Agency costs and post cross border acquisition performance of Malaysian acquires - Ibrahim, Yusnidah; Minai, Mohd Sobri; Hasan, Md Mahadi; Raji, Jimoh Olajide (Universiti Malaysia Sarawak, 2019)
The purpose of this paper is to investigate whether the variation in the performance of Malaysian acquirers following cross-border acquisition (CBA) activities is explained by agency costs factors. This study uses one, two and three years buy-and-hold abnormal return (BHAR) to measure acquisition performance and weighted least square regression to evaluate the impact of agency costs factors on acquisition performance. The findings suggest that the CBA performance is influenced by agency costs of the acquirers where those with lower agency costs, characterized by higher institutional ownership, higher board gender diversity, and higher board ethnic diversity perform better. The sample was restricted to CBAs in Malaysia, which limits the generalization of the findings to other countries.The results are reasonable to serve as guide to policy makers to make appropriate policy concerning the representation of female and various races on board of directors. The results could also guide in making appropriate investment policy decision that will result in long-term performance of acquiring firms.The novel contribution of this study is in terms of revealing the applicability of corporate finance theories in explaining CBA performance in emerging markets where CBAs are aggressively undertaken and high failure rates of CBAs are reported using long term datasets and robust performance measures and analyses.